Compulsory: education and the dispossession of youth in a prison school - Vaught, Sabina Elena (University of Minnesota Press, 2017)
Introduction: take no prisoners -- Outside -- With its institutions : the education state -- Keys : lock-up and juvenile prison -- The street : arterials of the white state -- Second possession : racial property and removal -- Home : a story in three parts -- Inside -- Compulsory schooling : inside the education state -- The architecture of discipline : personal safety and prison security -- Guilty by association : kinship and treatment -- Conclusion: futilities -- Acknowledgments -- Notes -- Index